(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article aimed to bring more possibilities into existence for one of the O. Henry’s texts, “The Gift of the Magi”, in terms of the application of metacognition concept. The idea of level was rooted in metacognition concept and was used to examine the text. The study found that there were two levels for a same thing in O. Henry’s text.